(untitled) (Fiep Bulletin - online, 2013)
Every human being passes throw the aging process and this is variable each one, but in all cases leads to the progressive loss of the functional capacities of the organism and physiologic changes that are limiting the functional capacity and mobility. Also, there is a decrease of the motor capacities, including the agility. High levels of this capacity are related to the reduction of injury risks, and a bigger functional capacity. But few knowledge is known about agility in elderly women and these needs that the present research was made, with the aim to appraise the performance of elderly, health and sedentary women in an agility test, the timed up and go test and consequently appraise this capacity in a functional work, predicting the mobility and balance. METHODOLOGY: 34 elderly women, with with 66,1±5,2 years old, healthy and sedentary, voluntarily participated of the study and they made the test, the timed up and go test means, get up of a chair, contour a cone, get back and sit as fast as he can, without run. RESULTS: The descriptive analysis showed that 23 elderly women showed a time below 10 seconds, 11 between 10,01 and 20 seconds, none of them did the above 14 seconds, and only 3 did it above 12 seconds. So, to 67,6% is possible classify like normal and 32,4%, like fragile elderly women or with deficiency, with good mobility. It’s possible to say that performance’s group is agile, but stars decrease compared to normal adult. However few are the studies that relates agilities tests and more studies need to be done to find this population profile, to leads the professionals